Ginsenoside Rh2 regulates cardiomyocyte autophagy-dependent apoptosis through the PI3K-Akt-mTOR signaling pathway to attenuate doxorubicin-induced cardiotoxicity - Youping Wu; Sheng Zhang; Liqiang Gu; Cong Xu; Xiaobo Lin; Hu Wang (Applied Biological Chemistry)
Abstract Doxorubicin (DOX)-induced cardiotoxicity has become a major concern and is considered a limitation for the use of DOX in oncology treatment. Ginsenoside Rh2 (Rh2) is a ginseng extract with anti-inflammatory, antioxidant and cell cycle regulating activities. The aim of this study was to investigate the mechanism of cardioprotective effects of Rh2 in DOX-induced cardiotoxicity. This study utilized network pharmacology to search for potential targets and pathways of Rh2 against doxorubicin-induced heart failure. The mechanism of Rh2 protection of myocardial tissue was further examined using a doxorubicin-formed rat model of heart failure. Network pharmacology predicted 128 potential targets for Rh2 treating to heart failure. Autophagy and apoptosis pathways play critical roles in Rh2 treatment of heart failure accessed by GO and KEGG enrichment analysis. Animal experiment results showed that Rh2 attenuated DOX-induced cardiotoxicity, normalized the morphology of cardiac tissue and reduced cardiomyocyte autophagy as well as apoptosis by up-regulation of the PI3K-AKT-mTOR signaling pathway to antagonize the effect of DOX on cardiomyocyte damage. These results suggest that Rh2 was able to inhibit DOX-activated autophagy signaling and apoptotic pathways in myocardial tissues and reduced cardiomyocyte apoptosis. It has potential effects to protect myocardial tissue as well as antagonize DOX-induced cardiotoxicity.